The Effect of Adding L-Ergothioneine in Culture Medium on Blastocyst Development Rates - Çizmeci, Sakine Ülküm; Yusuflu, Burakalp (Acta Scientiae Veterinariae, 2022)
Background: Oocytes and embryos produce energy through mitochondrial oxidative phosphorylation by using oxygen. The membrane structure of the embryo is mostly composed of unsaturated fatty acids, for this reason DNA fragmentation, apoptosis, and abnormal gene expression are shaped as a result of the lipid peroxidation during culture. Oxidative stress (OS) is one of the most important problems affecting the in vitro embryo development. Antioxidant supplementation to the culture medium has been an alternative way to reduce cell damage caused by oxidative stress in in vitro embryo production systems. In this study, it was aimed to determine the effect of L-ergothioneine on blastocyst development when added to the culture medium. Materials, Methods & Results: The material of the study consisted of oocytes aspirated from the ovaries of Holstein cows which were collected from the local slaughterhouse. The ovaries were delivered to the laboratory within 2-3 h in a thermos which provided a constant temperature of 25-30oC with physiological saline (0.9%) containing antibiotics. All follicles in the 3-8 mm range on the ovaries were aspirated using 20 G needle. The collected follicle fluid was filtered through filters with a pore diameter of 70 micrometers. Cells remaining in the filter were washed with OPU medium and transferred to the petri dishes. Fluids were examined under a stereomicroscope. The cumulus-oocyte complexes were classified, and A and B quality oocytes were included to the study (A, B, C, and D quality COC). Oocytes aspirated from the ovaries and collected later on were incubated in IVM medium for 22 h. After maturation, it was taken into IVF medium, semen was added and incubated for 20-22 h. Possible zygotes to be taken to the culture stage were transferred to culture (IVC) drops with (L-ergothioneine 100 µL/mL (n:121) added and without antioxidant (control (n:124)), and kept in the incubator for 6-7 days. Evaluated on the day 7. Differences in in vitro embryo production stages were evaluated with the Chi-square test. The study was run in 5 replicates each time, with at least 20 possible zygotes for per group being cultured. It was determined that 262 (87.33%) of a total of 300 oocytes undergoing in vitro maturation were matured. It was determined that 245 of the mature oocytes were fertilized (93.51%). The cleavage rates of the groups were determined as 87.60% and 86.29%, respectively. Eighty-two (33.47%) blastocysts were obtained from 245 zygotes taken into the culture stage, and the blastocyst rates in the groups were found to be 40.50% and 26.61%, respectively. After the study, it was determined that the statistical difference between L-ergothioneine and control in cleavage rates was insignificant (P > 0.05) and blastocyst rates was significant (P < 0.05) Discussion: Oxygen content above normal ratios can increase the formation of reactive oxygen species (ROS), particularly hydrogen peroxide (H2O2), hydroxyl radical (HO·), and peroxyl radicals (ROO·). The increased rate of ROS negatively affects the success of IVP in mammalian embryos. It was observed that L-ergothioneine, which has high antioxidant activity, improved blastocyst development rates, and higher blastocyst rates could be achieved compared to the control group. By investigating the use of L-ergothioneine in different doses, it was thought that the dose with the highest antioxidant activity could be added to the culture medium in in vitro embryo production and more blastocysts could be produced. Keywords: antioxidant, blastocyst, L-ergothioneine, in vitro.